Vitamin K Status and Lower Extremity Function in Older Adults: The Health Aging and Body Composition Study - Shea, M. Kyla (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: While low vitamin K status has been associated with several chronic diseases that can lead to lower extremity disability, it is not known if low vitamin K status is associated with worse lower extremity function. METHODS: Vitamin K status was measured according to plasma phylloquinone (vitamin K1) and dephosphorylated-uncarboxylated MGP (dp-ucMGP) in 1,089 community-dwelling older adults (mean ± SD age =74±3 years; 67% female). Lower extremity function was assessed using the short physical performance battery (SPPB), gait speed, and isokinetic leg strength. Linear regression and mixed models were used to determine the cross-sectional and longitudinal associations between vitamin K status and functional outcome measures. RESULTS: Cross-sectionally, higher plasma phylloquinone was associated with better SPPB scores and 20-m gait speed (p ≤ .05). After 4–5 years, those with ≥1.0nM plasma phylloquinone (the concentration achieved when recommended intakes are met) had better SPPB scores (p = .03) and 20-m gait speed (p < .05). Lower plasma dp-ucMGP (reflective of better vitamin K status) was associated with better SPPB scores and leg strength cross-sectionally (p ≤ .04), but not longitudinally. Neither measure of vitamin K status was associated with walking endurance or with the rate of decline in function. CONCLUSION: Older adults with higher vitamin K status had better physical performance scores at baseline, but data are less consistent longitudinally. Since lower extremity disability is a common consequence of multiple chronic diseases for which a role of vitamin K has been suggested, future studies are needed to determine if vitamin K supplementation could improve function in those with vitamin K insufficiency and clarify underlying mechanism(s).